Centrinės šiaurės žemaičių tarmės prozodija. Instrumentinis ir sociolingvistinis tyrimas - Mažiulienė, Irena Ieva (Kalbotyra, 1996)
The general acoustic image of the accent patterns of the central northern Žemaitian dialect shows that the decisive distinctive feature of the acute and circumflex tonemes is a change of phonation. The phonation of the acute syllables changes sharply and abruptly in contrast with a mellow and continuous flow of energy in the circumflected syllables. These features are signalled by the variations of pitch (fundamental frequency) and intensity. Most often, however, the pitch and intensity compensate each other and differentiate the tonemes almost in an equal manner. The traditional prosodic features are well preserved in the speech of the older generation, while the younger generation already tends to level the features of the accents (especially the specific traits of the acute intonation). These changes in the prosodic patterns mainly are caused by the influence of Standard Lithuanian (by early diglossy), tendencies in the internal changes of the dialect arisen in the distant past, and by the intermingling of different subdialects.